Bleeding Associated With Antiarrhythmic Drugs in Patients With Atrial Fibrillation Using Direct Oral Anticoagulants: A Nationwide Population Cohort Study - Victor Chien‐Chia Wu; Chun‐Li Wang; Yu‐Chang Huang; Hui‐Tzu Tu; Yu‐Tung Huang; Chang‐Fu Kuo; Shao‐Wei Chen; Kuo‐Chun Hung; Ming‐Shien Wen; Shang‐Hung Chang (Journal of the American Heart Association: Cardiovascular and Cerebrovascular Disease)
Background This study investigated drug–drug interactions in patients with atrial fibrillation taking both a direct oral anticoagulant (DOAC) and an antiarrhythmic drug. Methods and Results Using data from the National Health Insurance database (2012–2018), we identified 78 805 patients with atrial fibrillation on DOACs, with 24 142 taking amiodarone, 8631 taking propafenone, 2784 taking dronedarone, 297 taking flecainide, 177 taking sotalol, and 42 772 on DOACs alone. Patients with bradycardia, heart block, heart failure, mitral stenosis, prosthetic valves, or incomplete data were excluded. Propensity score matching compared those taking both DOACs and antiarrhythmic drugs with those on DOACs alone. There was an increased risk of major bleeding in patients concomitantly taking DOACs with amiodarone when compared with matched patients taking DOACs alone (hazard ratio [HR],1.13 [95% CI, 1.04–1.23]; P=0.0044), particularly in patients taking dabigatran (HR, 1.19 [95% CI, 1.03–1.38]; P=0.0175). No significant difference in bleeding risk was found for propafenone, dronedarone, flecainide, or sotalol. The small sample sizes in the flecainide and sotalol groups limit interpretation. Notably, intracranial bleeding risk was higher in patients on DOACs and amiodarone, regardless of age. Additionally, patients <80 years old taking dabigatran with amiodarone or propafenone had a higher risk of gastrointestinal bleeding. Conclusions Concomitant use of DOACs with amiodarone, but not dronedarone or propafenone, increases the risk of major bleeding, particularly intracranial bleeding. This study provides new evidence to guide clinicians to tailor concomitant anticoagulation and antiarrhythmic therapy for patients with atrial fibrillation.